Histological typing of soft tissue tumours - Weiss, S. W; Sobin, Leslie H (Springer, 1994)
The publication in the series are not intended to serve as textbooks, but rather to promote the adoption of a uniform terminology that will facilitatecommunication amoung cancer workers. For this reason, the literature references have intentionally been omitted and readers should refer to standard works for bibliographics.
International histological classification of tumours
Keywords: Neoplasms by Histologic Type; patologie; nádory podle histologického typu; onkologie; nádory měkkých tkání; Soft Tissue Neoplasms